2021
DOI: 10.1039/d0ra10810c
|View full text |Cite
|
Sign up to set email alerts
|

A modified random network model for P2O5–Na2O–Al2O3–SiO2 glass studied by molecular dynamics simulations

Abstract: (A) A modified structural model proposed for P2O5-bearing sodium aluminosilicate glasses. (B) Degree of preferred connection (DPC) of different T–O–T network linkage for LAP, MAP and HAP glass compositions with various P2O5 content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…For 5.17 mol% < P 2 O 5 content < 8.62 mol% (3 < x < 5), phosphorus broke the connection of Si–O BO –Si and Si–O BO –Al to form Si–O BO –P and Al–O BO –P linkages, indicating that the Si–O BO –P and Al–O BO –P linkages are energetically more favorable. It is also confirmed by Zhao's work 44 . They have found that Al–O–P and Si–O–Al linkages are preferred over other connections.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…For 5.17 mol% < P 2 O 5 content < 8.62 mol% (3 < x < 5), phosphorus broke the connection of Si–O BO –Si and Si–O BO –Al to form Si–O BO –P and Al–O BO –P linkages, indicating that the Si–O BO –P and Al–O BO –P linkages are energetically more favorable. It is also confirmed by Zhao's work 44 . They have found that Al–O–P and Si–O–Al linkages are preferred over other connections.…”
Section: Resultssupporting
confidence: 64%
“…It is also confirmed by Zhao's work. 44 They have found that Al-O-P and Si-O-Al linkages are preferred over other connections. Accordingly, phosphorus is more likely to connect to a stable SiO 4 tetrahedron and simultaneously generate Si-O BO -P linkages.…”
Section: Bo and Nbomentioning
confidence: 99%
“…In the phosphate-free glasses, sodium is assumed to act as charge-compensator for aluminate ([AlO 4 ] − ) groups. Here, each sodium ion is coordinated with approximately six or more BO ions, each belonging to Si–O–Si or Si–O–Al bonds (rather than a direct link between one Na + and one [AlO 4 ] − ). The key to interpreting the FIR band shifts is the first coordination shell of sodium.…”
Section: Resultsmentioning
confidence: 99%
“…Finally at x ≥ 15 they balance the charges of dianionic P 1 units, the formation of which eventually leads to devitrification and formation of crystalline sodium pyrophosphate. It is worth noting, that the structural scenario summarized in Figure is also consistent with recent MD simulation predictions for this system: Al–O–P and Al–O–Si connectivities dominate, while Si–O–P linkages are under-represented. Nonbridging oxygen species are formed preferentially on the phosphate rather than the silicate species.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated a low probability of P–O–Si linkage formation by 29 Si{ 31 P} and 31 P{ 29 Si} rotational echo double resonance (REDOR) spectroscopy. These results were qualitatively confirmed by a subsequent MD simulation study of a wide range of quaternary glass compositions, suggesting again a strong preference of Al–O–Si and Al–O–P linkages and a low probability of Si–O–P or P–O–P linking . These authors pointed out that such bonding preferences may lead to heterogeneity at the nanometric level and beyond, which becomes particularly pronounced for peralkaline glass compositions.…”
Section: Introductionmentioning
confidence: 99%